A Study on Phonological Process: A Case on Indonesian EFL Students’ Pronunciations - Mohamad, Hayria; Hanafi, Hanisah; Dako, Rahman Taufiqrianto (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2021)
The present article seeks to discuss the phonological process concerning the alterations in English sounds produced by Indonesian EFL students. This study drew on generative phonology and utilized Schane’s (1973) categories of the phonological process to highlight the changes in English sounds. This study applied a qualitative method with a descriptive research design. All data of this study were gathered through digitally recording eight EFL students’ oral presentations in the research proposal seminars. According to the results of this study, the transformations in the English sounds arose in both the consonant and vowel sounds of the English, where these changes attributed to the four categories of phonological process, including assimilation, dissimilation, deletion, and insertion. The present study also found the occurrences of a double and triple different phonological process in single word utterance produced by participants of this study. This study signified that such changes in English sounds occurred owing to the mother tongue influence. The results of this study offer a significant contribution to the insights into both linguistics and EFL instruction.